Drug policy - Plassmeyer, Mark (Handbook of forensic social work, 2024)
This chapter provides readers with a comprehensive understanding of how substances and the people that use them were criminalized over time and the current efforts to reverse that trend. It begins with an overview of the outcomes of the prohibition-based model. Then the major historical policies that led to the current drug control framework in the United States, along with some efforts at reform, are explored. Next, the chapter delves into alternative approaches to drug policy that consider drug use from a public health perspective. Notably, these policies aim to reduce the possible harms of drug use and redress the damages suffered by vulnerable people and communities during past approaches that were primarily based within the criminal legal system. The conclusion discusses the emerging drug policies and practices most in line with social work values and the need for social work to engage more meaningfully in shaping drug policy moving forward.